Outcome of CRH stimulation test and overnight 8 mg dexamethasone suppression test in 469 patients with ACTH-dependent Cushing’s syndrome - Detomas, Mario; Ritzel, Katrin; Nasi-Kordhishti, Isabella; Wolfsberger, Stefan; Quinkler, Marcus; Losa, Marco; Tröger, Viola; Kroiss, Matthias; Fassnacht, Martin; Vila, Greisa; Honegger, Jürgen Bernd; Reincke, Martin; et al. (Frontiers in Endocrinology, 2022)
Objective: To evaluate diagnostic accuracy of corticotropin-releasing hormone (CRH) stimulation test and overnight 8 mg dexamethasone suppression test (DST) for the differentiation of Cushing’s disease (CD) and ectopic Cushing’s syndrome (ECS). Methods: Retrospective study in 6 European centers. Inclusion criteria: patients with a) overt adrenocorticotropin (ACTH)-dependent Cushing's syndrome at the time of dynamic testing, b) histopathological confirmed tumors and/or c) postoperative biochemical remission and/or adrenal insufficiency. Optimal cut-offs were calculated via receiver operating characteristic (ROC) analysis. Results: 469 patients were analyzed (78% females; median age 43 years (IQR 19)). CRH test and overnight 8 mg DST were performed in 420 (CD, n=394 (94%); ECS, n=26 (6%)) and 237 patients (228 CD (96%), 9 ECS (4%)). Both tests were performed in 205 patients (44%)). The post-CRH %-increase at 30 minutes of both ACTH (cut-off ≥31%, sensitivity 83%, specificity 85%, AUC 0.81) and cortisol (cut-off ≥12%, sensitivity 82%, specificity 89%, AUC 0.86) discriminated best between CD and ECS. A test duration of >60 minutes did not improve diagnostic performance of the CRH test. The optimal cortisol cut-off for the %-suppression during the 8 mg DST was ≥55% (sensitivity 80%, specificity 78%, AUC 0.75). Conclusion: The CRH test has equivalent sensitivity but higher specificity than the 8 mg DST and is therefore the test of first choice. The diagnostic outcome of ACTH and cortisol is well comparable, however, sampling beyond 60 minutes post-CRH does not provide diagnostic benefits.